249 Effects of Heat Stress Mitigation Techniques on Feedlot Cattle Performance, Environmental, and Economical Outcomes in a Hot Climate. (7th December 2018) - Klopatek, S; Rivera, C; Gonzalez, A; Rotz, A; Mitloehner, F
Abstract: Heat stress in feedlot cattle is a major animal welfare and economic concern, costing the U.S. beef cattle industry up to $369 million annually. To mitigate the deleterious effects of heat stress on animal performance and feedyard productivity, a feedyard in central Mexico compared various cooling methods for finishing cattle. Using the Integrated Farm System Model (IFSM), a partial lifecycle assessment (LCA) was performed to determine economic returns and environmental footprints of various cooling methods. The two year feedyard study was arranged in a completely randomized design with four treatments and three replications/yr, with time as a block (n = 6). The four treatments included 1) conventional shade (control; SC; steel shade 1.8 m2 of shade/hd), 2) double conventional shade (DS; steel shade 3.6 m2 of shade/hd), 3) dome structures without fans (DSA; 8.5 m2/hd with 98% solar radiation blocked), and 4) domes with fans (DCA; three large sized low-speed fans). Each of the four treatments had 65 Bos indicus bulls, in a pen area of 570 m2. When compared to the control (DC), DCA improved final BW by 25 kg (P < 0.05), followed by DSA at 12 kg (P < 0.05), and DS at 5 kg (P> 0.05). When treatment results were extrapolated to the entire feedyard population (annual turnover of 209, 700 hd/yr), cattle in domed structures (DSA and DCA) versus steel shades (SC and DS) had reduced greenhouse gas (GHG) and ammonia (NH3) emissions on a kg of BW basis. Compared to the control (SC), DSA had the greatest economic return of $13.14/ hd, followed by DCA and DS treatments with a return profit of $7.47 and $7.03, respectively. Overall in this hot climate, the implementation of advanced shade structures improved cattle performance and profitability while reducing environmental impacts of beef production.